Association of gene polymorphisms in interleukin-6 with the occurrence of cerebral palsy in children with hypoxic-ischemic encephalopathy on birth - Putniković Dunja; Pančurov Aleksandra; Radojević Matija; Cerovac Nataša (Medicinski Podmladak, 2024)
Hypoxic-ischemic Encephalopathy (HIE) is one of the most common neurologic diseases in children and an important cause of cerebral palsy (CP). It is a permanent, non-progressive motor disorder that results in a delay in psychomotor development. Brain damage is followed by the activation of the immune system, and increased cytokine concentration in the plasma. Cytokines are circulating soluble proteins, mediators of communication for immune cells. The main biological activity of interleukin-6 (IL-6) is the stimulation of the liver to produce acute-phase proteins. Aim: The frequency of genotypes and alleles of the IL-6 gene polymorphism will be determined, analyzing the possible connection between IL-6 gene polymorphism and the onset of CP. Material and methods: This study involved 117 newborns who were treated in the Clinic of Neurology and Psychiatry for Children and Youth and the Clinic for Gynecology and Obstetrics of the University Clinical Centre of Serbia in Belgrade. Data was collected for each patient regarding their gender, gestational age, birth weight and Apgar score. Genotyping of rs1800795 in the IL-6 gene was performed by real-time PCR using a standardized TaqMan SNP assay. The difference in frequency of genotypes and alleles was analyzed by the X2 test. Results: The frequencies of genotypes in patients with CP were: 86.5% for GC + GG and 13.5% for CC, and in patients without CP were: 84.6% for GG + GC and 15.4% for CC. The frequency of alleles in patients with CP for G allele was 63.5% and for C allele 36.5%. In the group without CP, 56.2% had G allele and 43.8% C allele. No statistical significance has been demonstrated. Conclusion: No connection between IL-6 gene polymorphism with the development of cerebral palsy in newborns diagnosed with HIE at birth was demonstrated.